PEMBUATAN KATALOG WISATA SEBAGAI SARANA PROMOSI PARIWISATA DESA BATU PUTIH KECAMATAN SEKOTONG KABUPATEN LOMBOK BARAT - Nia Kurniati; Syaumudinsyah; Mey Susanti AS; Lubna (Yayasan Nusantara Hasana Berdikari, 2023)
Tourism is one of the economic sectors that contributes significantly to both GDP and GRDP. Tourism in NTB Province experienced a decline in visits during the Covid-19 pandemic. Lombok Island is a tourist destination that has great potential to be developed. One area in Lombok that has a lot of tourism potential is Batu Putih Village, Sekotong District, West Lombok Regency. Geographically, Batu Putih Village is a coastal village so most of its tourist destinations are marine tourism. Even though it has a lot of tourism potential, it still cannot increase the number of visits and help the community's economy. The partner's problem is the lack of understanding of the local community to develop and introduce tourism potential in their area, so that a media is needed to be able to introduce tourism to Batu Putih Village. The purpose of this community service activity is to introduce Batu Putih Village tourism to the public through catalog media. The results of this PKM activity are that several tourist sites displayed in the tourist log are tourism icons in Batu Putih Village which consist of Pao-Pao Beach, Kores Beach, Gelundung Beach, Bangko-Bangko Beach which is one of the well-known beaches to foreign countries for surfers. and also artificial tourism in the form of the Bendungan Tibu Kuning.